(untitled) (Homoeopathy for All, 2024)
In the current times, irritable bowel syndrome (IBS) has become one of the most frequently identified digestive disorders. It is a symptom based condition that can be identified by the presence of abdominal pain or discomfort together with abnormal bowel habits in the absence of any other underlying disease that would be responsible for these symptoms. Patients report chronicity of complaints experiencing stomach pain and abnormal bowel habits, primarily with constipation (IBS-C), diarrhoea (IBS-D), or mix of both (IBS-M). IBS is diagnosed clinically because there hasn’t been a conclusive investigation or any specific biomarker for its diagnosis.